Imaging and Radiomics of Immuno-oncology of Primary and Secondary Gastrointestinal Malignancies - Uhlig, Johannes; Biggemann, Lorenz; Sheth, Amar; Sharma, Rohini (Digestive Disease Interventions, 2020)
In recent years, systemic cancer treatment has been revolutionized with the advent of immunotherapy, which utilizes the body's immune system to target cancer cells and results in unique and novel imaging patterns of cancer response and therapy-associated toxicities. Hyperprogression is defined as a rapid tumor progression after treatment initiation. In contrast, pseudoprogression is defined as a tumor response after an initial increase in tumor burden, or appearance of new tumor lesions, and observed in <10% of patients undergoing PD-1/PD-L1 immunotherapy. Since traditional radiological strategies might not fully capture tumor response of patients receiving immunotherapy, several efforts have been made to better quantify specific immuno-oncological imaging patterns, including immune-related response criteria, immune-related RECIST, immunotherapy RECIST, and modified RECIST. These criteria account for potential pseudoprogression, and thus may prevent preemptive immunotherapy cessation. Immunotherapy is also associated with specific immune-related adverse events, including colitis (8–22% of patients), hypophysitis (8–13%), pneumonitis (<4%), lymphadenopathy (5–7%), hepatitis (1–7%), and pancreatitis (2%). Quantification of imaging studies using radiomic features has shown promising results in immuno-oncology, including prediction of individual patient's treatment response and survival, as well as characterization of tumoral expression of immunotherapy-relevant targets.
Keywords: immunotherapy; imaging; radiomics